The Moderating Role of Empathy Profiles in the Relationship Between Knowledge About Aging and Attitudes Toward Older Adults Among Nursing Students - Yao, Gui-Ying; Luo, Yan-Yan; Zhao, Zhi-Min; Zhu, Bo; Gao, Min (Frontiers in Psychology, 2021)
Knowledge about aging (KA) and empathy affect nursing students’ attitudes toward older adults. However, little is known about the mechanisms underlying this phenomenon from an integrated, person-centered perspective. The purposes of the present study were (1) to identify empathy profiles based on the Interpersonal Reactivity Index (IRI) among Chinese nursing students and (2) to explore whether these latent empathy profiles moderate the association between KA and attitudes toward older people. A cross-sectional survey design was used, and a battery of questionnaires—including those on demographic information, the Chinese version of Palmore’s Facts on Aging Quiz (C-FAQ), the Chinese version of Kogan’s Attitude Toward Older People Scale (C-KAOP), and the IRI—was filled in by 622 Chinese nursing students (Mage 21.76; SD = 1.33). The mean total scores on KAOP and C-FAQ were 164.96  18.32 and 10.436  3.015, respectively, indicating relatively positive attitudes toward older people but low KA among Chinese nursing students. Latent profile analysis was used to identify a three-profile solution characterized by distinct levels of four dimensions of empathy, namely average empathy (AE, n = 398), high empathy (HE, n = 42), and low empathy (LE, n = 181). Subsequent linear regression analysis revealed that the LE rather than the HE profile predicted positive attitudes toward older adults. It is worth noting that the LE profile played a remarkable moderating role in associations between KA and negative attitudes toward older adults after controlling for covariant variables. Both the identification of distinct empathy profiles and the interplay between the LE profile and KA are of significance in reducing negative attitudes toward older adults among Chinese nursing students. Nursing educators should combine improving nursing students’ levels of KA and fostering greater empathy to reduce negative attitudes toward older adults. Such training should give priority to nursing students with LE.